2018
DOI: 10.1088/1367-2630/aade66
|View full text |Cite
|
Sign up to set email alerts
|

Universal scaling behavior of the upper critical field in strained FeSe0.7Te0.3 thin films

Abstract: Revealing the universal behaviors of iron-based superconductors (FBS) is important to elucidate the microscopic theory of superconductivity. In this work, we investigate the effect of in-plane strain on the slope of the upper critical field H c2 at the superconducting transition temperature T c (i.e. −dH c2 /dT) for FeSe 0.7 Te 0.3 thin films. The in-plane strain tunes T c in a broad range, while the composition and disorder are almost unchanged. We show that −dH c2 /dT scales linearly with T c , indicating th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…The upper critical fields at 0 K (H C2 (0)) for all the superconducting samples have been estimated using the Ginzburg-Landau (GL) theory. The GL theory provides the analysis of the H C2 (0) values near T C [32]. The H C2 (T) versus T/T 90 plot for the calculation of H C2 (0) have been shown in the figure 7(a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The upper critical fields at 0 K (H C2 (0)) for all the superconducting samples have been estimated using the Ginzburg-Landau (GL) theory. The GL theory provides the analysis of the H C2 (0) values near T C [32]. The H C2 (T) versus T/T 90 plot for the calculation of H C2 (0) have been shown in the figure 7(a).…”
Section: Resultsmentioning
confidence: 99%
“…The H C2 (T) versus T/T 90 plot for the calculation of H C2 (0) have been shown in the figure 7(a). The GL equation (equation ( 1)) is given below [32,33].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure , the B (T) versus T (K) plots are in a small temperature range close to transition temperatures. The Ginzburg–Landau (GL) theory provides an analysis of the upper critical field values near the transition temperature . Therefore, in this work the B C2 (0) values are obtained by fitting the B C2 (T) versus T / T 90 (see inset of Figure ) curves with the GL equation (Equation )BC2(T)=BC2(0)(1t21+t2)where t = T / T C is the reduced temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The resultant films showed a Se content of around 0.7 because of the preference of Fe to bond with Se. Also Yuan et al found the resultant films showed a Se content of around 0.7 even though the PLD target with FeSe 0.5 Te 0.5 was employed [134].…”
Section: Pulsed Laser Deposition (Pld)mentioning
confidence: 99%